Prevalence, Incidence and Severity of Anthracnose in Carica Papaya Fruits in Baringo and Elgeyo-Marakwet Counties - Kugui, Kiprop; Mwamburi, Lizzy; Kiprop, Ezekiel; Kipsumbai, Pixley (African Journal of Education,Science and Technology (AJEST), 2020)
Papaya is the fourth most important fruit crop in Kenya after oranges, mangoes and bananas. It has also become an important export crop in the arid and semi-arid lands. Anthracnose caused by Colletotrichum gloeosporioides in pawpaw (Carica papaya) infects pawpaw fruits both in the field and also under postharvest conditions resulting in huge economic losses. Therefore, information on the epidemiology of the disease and the extent of damage provides vital information for the management of the disease. Field surveys were conducted in major pawpaw-growing areas of Baringo and Elgeiyo-Marakwet Counties from March 2016 for 15 months during the fruiting stage, in order to determine the incidences, prevalence and severity of anthracnose disease. A total of 32 farms in 8 areas (4 farms per area), 20 in Baringo and 12 in Elgeyo-Marakwet, that had pawpaw at the fruiting stages were sampled in the two counties using the line transect method. In each farm a 9 m side of a ‘W’ shaped transect was used to assess the incidence of anthracnose on papaya. Significant differences (p =0.05) in disease prevalence in Carica papaya were reported in Baringo (95 %) and Elgeyo-Marakwet (83 %). The percent disease incidence of anthracnose infections on fruits was 9.23 ± 1.22 % in Baringo County and 4.5 ± 1.1 % in Elgeyo Marakwet County. The severity of anthracnose disease was higher in Baringo than Elgeyo Marakwet and was found to positively correlate with the incidence. In regions where lower incidences were reported, there was low severity of the anthracnose disease. In a severity scale of 1-5, the severity was predominant in the scale of 1 and 2. There is need to characterize the isolates of C. gloeosporioides infecting papaya in the two counties. Additionallya detailed study on influence of various ecological factors on the distribution and epidemiology of C. gloeosporioides are necessary in order to inform integrated disease management strategies of anthracnose of papaya in this region.